Influence of Monetary Benefits on Employee Performance in 3s Center, Valenzuela City: Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Employee performance is a major concern for businesses in today's competitive world. Theimpact of monetary benefits on employee performance is one of the important factors thataffect organizational performance. The purpose of this study is to examine the influence ofmonetary benefits on employee performance in 3S Center, Valenzuela City. Monetarybenefits are tangible rewards, such as salaries, bonuses, and incentives that employeesreceive from the organization. The study will look at how these monetary benefits positivelyor negatively influence employee performance, productivity, and motivation in the workplace.By understanding this relationship, organizations may be able to improve their employeeperformance and overall organizational success.The impact of monetary incentives on employee performance at 3S Center, Valenzuela City,or any work has been widely explored in the discipline of Human Resource Management(HRM). Employers frequently utilize monetary rewards such as salaries, bonuses, and otherincentives to encourage and keep their staff. The researchers concluded that monetaryadvantages had a beneficial influence on employee performance. Employees who are fairlycompensated and suitably recognized for their achievements are more engaged andproductive at work. On the other hand, employees who are underpaid or feelunderappreciated are more likely to be disengaged and may eventually quit their positions.However, it is important to note that monetary benefits are not the only factor that influencesemployee performance. Other elements that influence employee motivation andperformance include job happiness, work environment, and opportunity for growth anddevelopment. In conclusion, while monetary incentives are crucial in motivating and keepingpeople, they should be viewed as one piece of a broader jigsaw that incorporates otheraspects that influence employee performance.It has been up for discussion for a while now whether financial incentives have an effect onworkers' productivity. Some claim that monetary incentives are insufficient to increaseemployee performance, while others believe that monetary incentives are effectivemotivators. In the setting of 3S Center, Valenzuela City, monetary advantages may have asubstantial impact on employee performance. The automotive sector is highly competitive,and success depends on maintaining competent and motivated personnel. Offeringmonetary perks like bonuses and incentives may encourage employees to work harder andperform better. Despite this, it's critical to remember that financial rewards should becombined with a friendly and productive workplace. Simply throwing money at employeeswithout addressing underlying issues like stress, burnout, or a lack of communication maybackfire and result backfiring and resulting in lower morale and productivity. Finally, abalance of monetary and non-monetary incentives, such as professional developmentopportunities and recognition, may produce the best results in promoting employeeperformance and retention in 3S Center, Valenzuela City.